Mediating effects of information security awareness. Issue 106 (July 2021) - van der Schyff, Karl; Flowerday, Stephen
Abstract: Facebook users are often affected by privacy violations, many of which could be avoided by making adequate use of and periodically reviewing their privacy settings. However, despite frequent reports of privacy-related news and events, many users fail to periodically review these settings. In doing so, they remain vulnerable to privacy violations and perpetuate the cycle of privacy victimization. Given that an individual's personality influences their behavior it is important to understand which personality traits are more likely to adopt privacy-protective behavior as a function of increased information security awareness. Using select constructs from the theory of planned behavior (TPB), we evaluate the mediating role played by information security awareness in certain users' intentions to review their Facebook privacy settings. In particular how information security awareness mediates the relationships between each of the Big Five personality traits and their intention to review these settings. To perform the evaluation, we analyzed 594 survey responses using partial least squares path modeling (PLS-SEM). Our results indicate that information security awareness does act as a mediator, but only for some of the personality traits. In particular we found information security awareness to act as an indirect mediator between openness and intention to review privacy settings . This indicates that as users high in openness increase their awareness of privacy-related threats (via privacy news and events), so their intention to review privacy settings increases. We also found information security awareness to mediate the relationship between conscientiousness and intention to review privacy settings – albeit in a complementary manner. No mediating evidence was found for extraversion, neuroticism, and agreeableness .